Analisis Dampak Judi Online Pada Se’orang Tiktokers : ( Nafdan/ Fahdan Naufan Fadhil ) - Ika Ayu Nurlela; Aora D’laninduhan Fiem; Doan Widhiandono (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The aim of this research is to determine the negative impact of online gambling in the current era, especially on the younger generation. We use this research method as a qualitative method, where we as researchers carry out an analysis by observing various digital media platforms, from which we can find out the various negative impacts experienced by several young people today due to carrying out online gambling transactions. We took the case example of a TikTok celebrity named Fahdan who shared a story about the other side of online gambling that not many people know about. From this case, we as researchers concluded that in fact online gambling has more negative impacts than positive ones.